Under What Conditions Do Outward FDI of Emerging Market Enterprises Enhance Innovation Performance? - Su, Jiaoyue (2019)
This paper provides some new ideas in understanding the relationship between the internationalisation of EMEs and their innovation outcomes. Due to the dramatic economic development of emerging economies, emerging market enterprises (EMEs) have increasingly participated in the internationalisation process like their counterparts in the developed markets (Godwin and Cook 2018). Although extant research and empirical studies have focused on the motives and strategies of the internationalisation of EMEs, the innovation performance of internationalized EMEs has received limited attention. While outward FDI of EMEs can enhance their innovation performance, this relationship is moderated by a series of third variables. This paper proposes three factors that may positively or negatively moderate the focal relationship, which are the speed of internationalisation, state ownership, and sub-national institutional distance. The internationalisation process model, organisational learning theories, and institution-based view are used to frame the analysis.